Áreas de risco de erosões do tipo movimento de massa do solo em Lagoa Dourada, Minas Gerais - Brasil - Lima, Victor Henrique Resende (2021)
The identification of erosion risk areas, such as soil mass movements in urban centers, is of paramount importance for the prevention of socio-environmental disasters. Thus, the objective was to identify areas with potential risks of erosion by soil mass movement in the urban perimeter of Lagoa Dourada - Minas Gerais, Brazil. In this study, slope data structured in grid in the GeoTiif format of the TOPODATA portal were used, aiming at the identification of risk areas located in the urban perimeter of the municipality Lagoa Dourada, Minas Gerais - Brazil. To perform image processing, conversion to vector files and map generation, QGIS software version 3.10.5, open source GIS, was used. Locations with slopes between 20 and 30% and those above 30% were considered, respectively, as "Strong" and "Very Strong" risk of erosion by soil mass movement. There was an area of 577.385 ha considered at erosion risk, representing 46.11% of the total study area, most of the erosion risk areas was located around the urban perimeter of the municipality, occurring in expressive quantities in Cambisolos (256.239 ha, representing 44.39% of the erosion risk areas), even with less coverage in the area when compared to Latosols (321.130 ha, representing 55.61% of the erosion risk areas). The high rainfall depth in the beginning of 2020, caused significant mass movements in the municipality, and most of these displacements were in areas classified as being at erosion risk, which demonstrated that the slope intervals used were adequate and can assist in prevention socio-environmental disasters and urban planning.